Estudo da adsorção de eteraminas de soluções aquosas pela bucha vegetal (Luffa Cylindrica) em sistema batelada - Karla Brandão Franco (2019)
Reverse cationic flotation is a separation process widely applied in the mineral industry for the concentration of ores. Etheramine is a reagent used as collector and foaming in iron ore flotation, allowing the separation of quartz from hematite, the interest mineral. Since the disaster of the Fundão Dam, diverse inquiries on the toxicity of the tailings and the associated liquid phase have been intensified, as well as the toxicity of the other reagents used in the mineral processing. The impacts mitigation and bioremediation when it occurs inappropriate discharge of these wastes into watercourses is of paramount importance aiming at keeping the good quality of hydric resources. In addition, the treatment of effluents containing these substances aiming at the reuse of water in the process can increase the environmental performance of the mineral activity. This work aims to study the affinity of vegetal sponge (Luffa Cylindrica) to remove etheramines from pure aqueous solutions and also those contained in wastewater from lab scale iron ore flotation, aiming to get sustainability at both the treatment of the effluent and the development of natural biofilters for water bodies bioremediation. The Luffa cylindrica was prepared by cutting the dried sponge into pieces of about 3 cm, washed in three stages with 10 g/L of solid liquid ratio in distilled water at 25oC. The release of organic compounds from washing step was performed by chemical oxygen demand (COD) measurements. Adsorption tests with 200 mg/L of etheramine at various adsorbent/solution ratios allowed the choice of the 4 g / L condition for the subsequent studies. The pH was varied in 7.5; 9.5 and 11.0 as well as it was the initial concentration of etheramine for both the kinetic study and the determination of adsorption isotherms at 35oC. The effect of the presence of starch in the solution was also evaluated. Adsorption tests with an effluent from bench scale flotation test were performed and the residual solution was also submitted to adsorption tests. The amine quantification was performed by the chloroform extraction method and colorimetric analysis with bromocresol green. The COD was also measured throughout the experiments. Up to 95% removal of etheramine and a maximum adsorption capacity of 41.02 mg/g at pH = 9.5 and 35°C were obtained. An ajust of R2=0.993 for the pseudo-second order kinetic model was obtained, at the same time for the pseudo-first order the graphic ajust of R²=0.991 could not affirm the slower step to this reaction. Instead of the Elovich model analysis allow to conclude that quimissorption is not the best model, since R²=0.988 was obtained. An equilibrium time of 60 min was chosen for adsorption isotherms experiments. The isotherms models proposed by Freundlich and Temkin showed very similar graphical adjustments providing correlation coefficients equal to R2 = 0.957 and R2 = 0.958, respectively. The curve in the S format, supplementary to the obtained results, indicated the formation of multilayers as well as the electrostatic interaction between adsorbate molecules which were favoured by the increase in pH and also by the increase of the etheramine concentration. The starch usually used as a depressant in the flotation showed a positive result in the adsorption of the etheramine. However, when the bench scale flotation effluent was used, the removal of etheramine was lowered, and 61% removal was observed in pH = 11.0, 4 g/L of vegetable sponge at 35oC. The present study grants positive and encouraging results aiming at the use of a renewable vegetal resource, with possibility to stimulus other economic sectors associated to the treatment of effluents and bioremediation of water bodies contaminated with residual reagents from iron ore processing when flotation is used as the concentration method.